Alkanediamide-Linked Bisbenzamidines Are Promising Antiparasitic Agents - Jean J. Vanden Eynde; Annie Mayence; Madhusoodanan Mottamal; Cyrus J. Bacchi; Nigel Yarlett; Marcel Kaiser; Reto Brun; Tien L. Huang (MDPI AG, 2016)
A series of 15 alkanediamide-linked bisbenzamidines and related analogs was synthesized and tested in vitro against two Trypanosoma brucei (T.b.) subspecies: T.b. brucei and T.b. rhodesiense, Trypanosoma cruzi, Leishmania donovani and two Plasmodium falciparum subspecies: a chloroquine-sensitive strain (NF54) and a chloroquine-resistant strain (K1). The in vitro cytotoxicity was determined against rat myoblast cells (L6). Seven compounds (5, 6, 10, 11, 12, 14, 15) showed high potency against both strains of T. brucei and P. falciparum with the inhibitory concentrations for 50% (IC50) in the nanomolar range (IC50 = 1-96 nM). None of the tested derivatives was significantly active against T. cruzi or L. donovani. Three of the more potent compounds (5, 6, 11) were evaluated in vivo in mice infected with the drug-sensitive (Lab 110 EATRO and KETRI 2002) or drug-resistant (KETRI 2538 and KETRI 1992) clinical isolates of T. brucei. Compounds 5 and 6 were highly effective in curing mice infected with the drug-sensitive strains, including a drug-resistant strain KETRI 2538, but were ineffective against KETRI 1992. Thermal melting of DNA and molecular modeling studies indicate AT-rich DNA sequences as possible binding sites for these compounds. Several of the tested compounds are suitable leads for the development of improved antiparasitic agents.